Mechanisms of resistance to KRASG12C inhibitors in KRASG12C-mutated non-small cell lung cancer - Chour, Ali; Toffart, Anne-Claire; Berton, Elodie; Duruisseaux, Michael (Frontiers in Oncology, 2024)
The KRAS protein, a product of the KRAS gene (V-ki-ras2 Kirsten rat sarcoma viral oncogene homolog), functions as a small GTPase that alternates between an active GTP-bound state (KRAS(ON)) and an inactive GDP-bound state (KRAS(OFF)). The KRAS G12C mutation results in the accumulation of KRASG12C(OFF), promoting cell cycle survival and proliferation primarily through the canonical MAPK & PI3K pathways. The KRAS G12C mutation is found in 13% of lung adenocarcinomas. Previously considered undruggable, sotorasib and adagrasib are the first available OFF state KRASG12C inhibitors, but treatment resistance is frequent.In this review, after briefly summarizing the KRAS pathway and the mechanism of action of OFF state KRASG12C inhibitors, we discuss primary and acquired resistance mechanisms. Acquired resistance is the most frequent, with "on-target" mechanisms such as new KRAS mutation preventing inhibitors binding; and "off-target" mechanisms leading to bypass of KRAS through gain-of-function mutations in other oncogenes like NRAS, BRAF, RET; or loss-of-function mutations in tumor suppressor genes like PTEN. Other "off-target" mechanisms described include epithelial-to-mesenchymal transition and histological transformation. Multiple co-existing mechanisms can be found in patients, but few cases have been published.We highlight the lack of data on non-genomic resistance and the need for comprehensive clinical studies exploring histological, genomic, and non-genomic changes at resistance. This knowledge could help foster new treatment initiatives in this challenging context.